Determinants of Hypertension in Poltekkes Kemenkes Jakarta III Students in 2022 - Mustikasari, Nina; Hanna, Henny; Nuryati, Tati (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Hypertension is the leading cause of death in the world every year. The high prevalence of hypertension, especially at a young age, is a major health problem that must be faced by the government. Hypertension that is not treated immediately will increase the risk of cardiovascular disease and can cause coronary heart disease, heart failure, stroke and transient ischemic attack earlier. This study generally aims to get an overview of the incidence of hypertension and to find out the related factors and the factors that most dominantly influence the incidence of hypertension among students at the Poltekkes Kemenkes Jakarta III in 2022. The method used in this study was a cross-sectional study with a purposive sampling technique to obtain a total of 107 respondents. Retrieval of respondent data is done by direct examination and filling out questionnaires that have been tested for validity and reliability. The results of the univariate analysis showed that most of the respondents were a female sex of 61 people (57%) with a prevalence of hypertension and prehypertension of 39 people (36.5%). 81 people (75.7%) do not have hypertension, smoke 20 people (18.7%), have abnormal body fat percentage 38 (35.4%), are inactive 39 people (36.4%) experienced stress as many as 41 people (38.3%) and all of them did not consume alcohol. In the results of bivariate analysis using the Chi-Square analysis test, it was found that there was a relationship between smoking (0.000), percent body fat (0.000), sex (0.001) and the incidence of hypertension in Poltekkes Kemenkes Jakarta III students. The results of multivariate analysis using logistik regression showed that percent body fat and smoking were the most dominant risk factors for hypertension in respondents. Each with a significance value of 0.000 and 0.013. Respondents with abnormal body fat percentage had a 7,098 chance and respondents with smoking habits had a 5,428 chance of experiencing hypertension. The conclusion is that percent body fat and smoking habits are the most dominant independent variabels in the occurrence of hypertension in Poltekkes Kemenkes Jakarta III students in 2022.